Deposit of Amphorae in the Quarter of St. Theodore, Pula - Starac, Alka (Archaeopress Roman Archaeology Ser., 2021)
This book examines a large group of amphorae from the quarter of St. Theodore in Pula, Croatia, used for drainage and levelling as part of the construction of the terrace of the Roman temple complex and adjacent public thermae. Investigations in 2005-2007 uncovered 2119 amphorae, of which 1754 were extracted and thoroughly documented.